The MX2Lx matrices, with M = Zn2+, Cd2+, Hg2+, X = Cl−, Br−, I− and L = pyrazine, quinoxaline, phenazine. Issue 4 (16th February 2017) - Slabbert, Cara; Rademeyer, Melanie
Abstract: Three structures combining the ditopic organic ligand quinoxaline with divalent metal halides MX2, with M = Cd 2+ and Hg 2+, are reported. All three structures are coordination polymers, with the quinoxaline ligand acting as organic linker between metal centers. In two structures, with M = Hg 2+ and X = Cl − or Br −, the formation of a 1-D, halide-bridged polymer in addition to the quinoxaline coordination polymer increases the dimensionality of the structure to 2-D, while in the case of M = Hg 2+ and X = Cl −, the formation of two halide-bridged polymers along with the coordination polymer results in the creation of a 3-D structure. Structural trends are identified, and the templating effect of the organic ligand is highlighted, through horizontal and vertical comparisons of these structures with related structures reported in the literature obtained upon combining the said metal halides with the related organic ligands pyrazine, quinoxaline, and phenazine, presented as the resulting matrices of structures. Abstract :